Increasing Compressive Strength of Self Compacting Concrete with MasterGlenium and MasterSure - Sefiyanti, Redyka; Mahardana, Zendy Bima; Rahmawati, Apriliya Laily; Husna, Nadiya; Zakiya, Zaizafun; Naufalanto, Hafiizh; Yuantono, Tegar Bhakti (UKaRsT, 2024)
The growth in development complexity demands innovation in the construction industry. Self-compacting concrete (SCC) can flow and fill mold cavities without additional vibration, offering an efficient solution for structures with complex shapes or tight spaces. In addition, SCC can speed up bonding and simplify workability by adding MasterGlenium and MasterSure superplasticizers. However, its use is limited due to a lack of understanding of the optimal composition of the mixture. The research aims to determine the effect of adding MasterGlenium and Maste Sure in the concrete mixture on the compressive strength of concrete. Experimental research was conducted with a mixture of MasterGlenium additives at 0.25%, 0,30%, 0,35%, 0.40%, and MasterSure 0.30% of the total binder. Slump and compressive strength tests of concrete are carried out to determine workability and quality performance. The research results showed that the optimal concrete mix with the addition of MasterGlenium 0.35% and MasterSure 0.30% was 25.39 Mpa, higher than Normal concrete 15.21 Mpa. The slump test results confirm that the concrete is classified as SCC. This shows the importance of the composition of MasterGlenium and MasterSure superplasticizers on the compressive strength of SCC concrete. So, the results of this research can be used to improve the quality of concrete structure projects.